PENGARUH KEPERCAYAAN DAN MEDIA SOSIAL TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN E-COMMERSE FASHION MUSLIM HIJAB DI JAKARTA - Ria Aprillia; Resa Nurlaela Anwar (Jurnal Manajemen Bisnis Krisnadwipayana, 2018)
Internet has an important role to support the development of e-commerce to make online transaction. Many online shopping stores open and making people more often make the purchase decision for a product. Social media has played a critical role in the evolution of online shopping. Consumers turn to social media for help and decided to bought something because they saw it on social media. In the purchase decision there are several factors that support is trust and social media, with these two factors a person is able to take the decision to purchase the product or not. This type of research with a quantitative approach. The population in this study are the consumers of Hijup.com but it is not known exactly how many Hijup consumers so that the sampling technique used is non-probability sampling. Methods of data collection are done by giving questionnaires online. Data processing conducted with technique of multiple regression analysis to test the hypothesis simultaneously and partially. The results showed that significantly influence of trust toward buying decisions on Hijup customer and media social significantly influence toward buying decisions on Hijup customers.